WARISAN AGUNG GAJAH MADA: MENYINGKAP KEJENIUSAN KEPEMIMPINAN DAN KECEMERLANGAN STRATEGI KERAJAAN MAJAPAHIT - Putra, Galih; Midhio, I Wayan (JURNAL ELEKTROSISTA, 2023)
This research delves into the captivating historical figure of Gajah Mada, exploring his leadership prowess and strategic acumen within the context of the Majapahit Empire. By focusing on understanding the impact and legacy of his leadership, this study synthesizes existing scholarly works, analyzes primary sources, and applies relevant theories to unravel Gajah Mada's remarkable qualities and achievements. By examining his traits, visionary approach, and ability to unite diverse regions, this research sheds light on the profound lessons and insights derived from his leadership style. Moreover, by critically evaluating his strategic thinking, military campaigns, diplomatic endeavors, and economic policies, this study unveils the fascinating story of Gajah Mada and his indelible mark on Indonesian history. The findings of this research contribute to a deeper understanding of leadership and strategic thinking while emphasizing the enduring significance of Gajah Mada's legacy in shaping the Majapahit Empire and the subsequent course of Indonesian history.